Penerapan Corak Tafsir Falsafi-Ontologis Terhadap Ayat Ketuhanan Dalam Surah Al-Ikhlas - Alif Rizky Ramadhan (Al-Fanar: Jurnal Ilmu Al-Qur’an dan Tafsir, 2023)
Al-Qur’an was coming with two kinds of system, the textualizes system and contextualize system or Tafsir. While people tend to use Qur’anic Tafsir as what the hadith and shahabi said. Some of the Islamic scholar uses a new kind methodology to interpret the Qur’an. It leads us to a whole new kind of Tafsir in Islamic community and one of them is known as philosophical Tafsir. This methodology insists that Al-Qur’an can be interpreted with a philosophical view in it. After a while, this methodology is partially abandoned by the Islamic scholar and deemed as a wrong way to interpret the holy Qur’an. Within the century, the philosophical work gradually changes from rational skepticism to value free philosophical work where rationalism alone is not working anymore. This new kind of trend, let the ontology system change rapidly from the system of though to system of critique. Now with this philosophical evolution came by, Islamic scholar need to review again the philosophical tafsir as Al-Qur’an methodology.